Accounting demystified : a self-teaching guide - Hart, Leita. 4 0 16; 5 (New York : McGraw-Hill, 2006)
Presents an introduction to accounting, providing information on balance sheets, income statements, cash flow, tax systems, quarterly reports, annual reports, debits versus credits, and more.
Includes index.
Young Adult;Young Adult
Keywords: 2 -- 0; 6; Accounting.;Accounting.; 20; 2